Designing and implementation of robot mapping algorithm for mobile robot - Ismail , Amelia Ritahani; Desia, Recky; Zuhri, Muhammad Fuad Reza; Daniel, Raja Muhammad (2014)

(untitled)
.A mobile robot is an automatic machine that is capable of movement in any given environment [1]. The Capabilities of Mobile Robot(s) are: Moving around based on the user’s input, Avoiding obstacle in front of it and Calculating the path.